the covid-19 pandemic as a force majeure reason for flight service users based on Law No. 1 of 2009. - Iwan Widi Setiawan; Levina Yustitianingtyas (Academos, 2023)
The unprecedented COVID-19 pandemic has caused people all over the world to panic. The World Health Organization (WHO) is taking proactive measures to prevent the spread of the virus, by directing countries around the world to take measures such as social distancing, physical distancing, quarantine, and regional restrictions or known as lock down which ultimately affects various sectors of life. This research discusses the covid-19 pandemic as a force majeure reason for flight service users based on Law No. 1 of 2009. This paper focuses on the issue of how the airline's responsibility for the unilateral cancellation of the Covid-19 reason based on Law No. 1 of 2009, and how is consumer legal protection for unilateral departure cancellations by airlines on the grounds of covid-19. This writing uses normative juridical research methods with data collection and is more emphasized on secondary sources of material, in the form of laws and regulations, examining legal principles and legal science theory. While the specifications in this study are descriptive analysis and analyzed by qualitative methods. This study seeks to analyze and answer problems regarding the COVID-19 pandemic as a force majeure reason for flight service users based on Law No. 1 of 2009.